Spatial access to in-patient health care in northern rural India - Vikram Ranga; Pradeep Panda (Geospatial Health, 2014)
Access to health care in rural areas is a major concern for local populations as well as for policy makers in developing countries. This paper examines spatial access to in-patient health care in northern rural India. In order to measure spatial access, impedance-based competition using the Three-Step floating Catchment Area (3SFCA) method, a modification of the simple gravity model, was used. 3SFCA was chosen for the study of the districts of Pratapgarh and Kanpur Dehat in the Uttar Pradesh state and Vaishali in the Bihar state, two of India’s poorest states. This approach is based on discrete distance decay and also considers more parameters than other available methods, hence is believed to be a robust methodology. It was found that Vaishali district has the highest spatial access to in-patient health care followed by Pratapgarh and Kanpur Dehat. There is serious lack of health care, in Pratapgarh and Kanpur Dehat with 40% and 90% of the villages having shortage of in-patient care facilities in these respective districts. The most important factor affecting spatial access was found to be the distance to the nearest major urban agglomeration.